Effect of Job Insecurity, Workload, Employee Turnover Intention on the Work Environment at PT Tayoh Sarana Sukses - Feby Ningrum; Achmad Fauzi; Faroman Syarief; Annisa Nurchotimah; Ivan Adi Nugraha; Mochammad Ainun Zulfikar (Journal of Accounting and Finance Management, 2021)
The purpose of the research is to identify the impact of Job Insecurity, Workload, Turnover Intention on the Work Environment. Employees of PT. Tayoh Sarana Sukses research is the object of this quantitative research. A total of 100 respondents as a sample in this research. This study uses "Structural Equity Model (SEM)"-SmartPLS 3.0 for hypothesis testing. The results of the analysis show that job insecurity has a positive and significant impact on the work environment. Workload has a positive and significant impact on the work environment. And Turnover intention has a negative and significant impact on the work environment. So the conclusion from the findings of this research is that job insecurity, workload, turnover intention have a significant impact on the work environment.